2012
DOI: 10.1111/j.1750-8606.2012.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Relating Prenatal Testosterone Exposure to Postnatal Behavior in Typically Developing Children: Methods and Findings

Abstract: Testosterone levels during early development influence subsequent sex‐typical behavior. These influences were initially identified in experimental research on nonhuman species. Additional research—primarily investigating individuals exposed to atypical hormone environments due to genetic disorders or maternal treatment with hormones during pregnancy—suggested that testosterone also influences the development of sex‐typical behavior in humans. There is also interest in identifying relations between normal varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
(60 reference statements)
2
36
0
Order By: Relevance
“…There is a theory that during the prenatal period, having an opposite-sex co-twin can change the level of prenatal testosterone, resulting in differentiated brain structure and masculinization of girls (Tapp et al, 2011;Ahrenfeldt et al, 2015). This means that girls from opposite-sex pairs are more likely to pursue activities linked to the development of spatial abilities (Berenbaum et al, 2012;Constantinescu & Hines, 2012) and have fewer differences from boys in mathematical ability and mathematical achievement (as found in our study). Thus, biological factors related to the formation of mathematical ability could be linked with sex differences as well.…”
Section: Discussionsupporting
confidence: 60%
“…There is a theory that during the prenatal period, having an opposite-sex co-twin can change the level of prenatal testosterone, resulting in differentiated brain structure and masculinization of girls (Tapp et al, 2011;Ahrenfeldt et al, 2015). This means that girls from opposite-sex pairs are more likely to pursue activities linked to the development of spatial abilities (Berenbaum et al, 2012;Constantinescu & Hines, 2012) and have fewer differences from boys in mathematical ability and mathematical achievement (as found in our study). Thus, biological factors related to the formation of mathematical ability could be linked with sex differences as well.…”
Section: Discussionsupporting
confidence: 60%
“…The study found that female guinea pigs that were exposed to testosterone prenatally showed masculinized behaviour in adulthood. Since then, several studies of non-human mammals have demonstrated effects of testosterone on neurobehavioural sexual differentiation (Constantinescu and Hines, 2012). Evidence that testosterone also influences human neurobehavioural development is to a great extent derived from studies of individuals who develop in atypical hormone environments (Constantinescu and Hines, 2012), and the best-studied clinical condition is congenital adrenal hyperplasia (CAH) (Cohen-Bendahan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies of non-human mammals have demonstrated effects of testosterone on neurobehavioural sexual differentiation (Constantinescu and Hines, 2012). Evidence that testosterone also influences human neurobehavioural development is to a great extent derived from studies of individuals who develop in atypical hormone environments (Constantinescu and Hines, 2012), and the best-studied clinical condition is congenital adrenal hyperplasia (CAH) (Cohen-Bendahan et al, 2005). Females with CAH, who produce high levels of adrenal androgens from early in gestation due to an autosomal recessive disorder, show increased male-typical behaviour and decreased female-typical behaviour despite postnatal hormone treatment (Hines, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is no shortage of complex explanations to envision how sex, primarily through its endocrine influences on the developing brain, may modulate the propensity to develop a neuro-developmental disorder like autism (Bale et al, 2010; Connors et al, 2008; Marco, Macri, & Laviola, 2011). Fetal testosterone (fT) plays a central role in human neurobehavioral sexual differentiation and in later social behavior (Bergman, Glover, Sarkar, Abbott, & O’Connor, 2010; Constantinescu & Hines, 2012). Thus, elevated testosterone exposure during critical periods of early development might be responsible for permanent behavioral changes.…”
mentioning
confidence: 99%